Overcoming Barriers: De-Tracking to Teach for Social Justice - Stephanie J White (Middle Grades Review, 2021)
How do we overcome tracking in mathematics to actualize the goals of teaching for social justice? Tracking is a racist educational structure that puts limits on the effectiveness of teaching for social justice. This essay presents arguments for de-tracking with explanation of how tracking negatively impacts Black and Latinx students. Readers will learn about schools and districts that have de-tracked students juxtaposed with the barriers that keep most schools from dismantling tracking. This essay calls upon schools and researchers to further investigate locally why schools do not work through these barriers to spark action and eliminate tracking.
Keywords: mathematics; tracking; de-tracking; teaching for social justice